Мodeling of stressed-deformed state in mechanical tasks soils - Білеуш, А.І.; Прусов, Д.Е.; Веремієнко, В.К.; Вощило, О.В. (Proceedings of National Aviation University (archive), 2006)
The modeling methods of heterogeneous and anisotropic soil mass taking into consideration real behavior have been carried out analysis by strain-stress state investigation on the basis of finite element method for assurance reliability.